THE BASIC COMPONENTS OF SUCCESSFUL LEADERSHIP IN SPORT - Radovan Čokorilo (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
Leadership is the most important factor of the structure and dynamics of each organised group. In the broadest sense of the word it is studied as an interactive process which affects individuals and groups in terms of implementation of the set goals. Leadership affects orientation of a group, exchange of information, decision making, establishment of interpersonal relations, people's motivation, etc. One should make a difference between a leader and a manager who is primarily in charge of planning, organisation, budget, assistant personnel etc. Even though leaders sometimes have the same obligations, leadership involves the skill of vision embodiment and not only a specific style of behaviour. Methods: It is primarily used descriptive, analytical and synthetic methods by which we critically anlizirali phenomenon of leadership in the sports group and different approaches in his study. In connection with this leadership was observed as an important multidimensional conditioned interactive process in the sports group. Results: Summative results of different approaches to analysis of leadership in sport have shown that no single approach can be labelled as the best one however, understanding advantages of each one of them enables us to understand better the thing that makes leadership successful. The most important proven factors of efficient leadership are leader's quality, followers' quality, situational factor and leadership style. Discussion: The most important quality leaders have proven integrity, flexibility, responsibility, self-discipline and patience. They should be viewed in the context of democratic and autocratic style of leadership. Situational and environmental factors (type of sport, the number of teams, team interactivity ...) determine the importance of certain personality traits and leadership style choice. Finally, the quality of group members largely determines the success of a leader. The need for blending style leaders and participants highlighted the importance of the interaction processes for successful leadership.